The Agreement on Trade-Related Aspects of Intellectual Property Rights (STRIPS) in the Algerian legislation in the field of pharmaceutical patents - Mermoune, Moussa (Journal of Human Sciences, 2020)
The world has recently witnessed considerable technological development in various areas of life as a result of modern inventions made in various fields of human activity. It was natural for the effects of this development to be reflected in international efforts that treated patent protection as the basis for this progress, which led to the conclusion of numerous international treaties and agreements. However, the creation of a comprehensive patent regulation as a coherent unit was only achieved with the emergence of the Agreement on Trade-Related Aspects of Intellectual Property Rights (STRIPS), where the most influential role was in this area, with the integrated protection added in terms of patents and the rights deriving from them. Its influential and pioneering role in this field is perhaps due to the principles established by this agreement and the provisions it introduced in a way that profoundly changed the characteristics of international regulation in the field of intellectual and industrial property in general, and patent protection in the field of pharmaceutical industries in particular.